PROTOTYPE INFORMASI LAHAN PARKIR MENGGUNAKAN ARDUINO - Tejo P, Yulianto; Edward A., Suyanto; Widyarto N., Erdhi (PROXIES, 2012)
The parking area is one of the main means of shopping centers, offices ami recreation areas. The accurate information about a parking area will be very important for users. This paper will explain about a prototype of parking area that give the user information of the capacity, the amount of the used space, and lamp indicator in each location of parking spaces. Users can find an empty space for parking in easy way because they just looking for IIzmp imJicator which on in each floor. This information system of parking area use the Arduino for processing the informaTtion from sensors that installed on each parking space. Besides to the LCD display, Arduino sends the information of empty space to the server in serial data form via USB connection. Using JQUERY application, the server will provide this information to the client in the website. So that the client will get information in real time.